Capital gain, real wages and labor efficiency in the manufacturing sector in Colombia (2014)
This paper aims to find empirical evidence on the positive relationship that is woven between wages and labor productivity for the Colombian manufacturing industry. This relationship is based onthe theory of nutritional status of Leibstein (1957) as well as the conjecture of the relationship between wages and the value of the labor force of Marx (1946). To this purpose a production function augmented on wages with panel data was estimated and found the wage of production operative and laborer affects their productivity. With the wage elasticity estimated the effect on the benefits of a policy increase of 1 % of salary was simulated. It was found that 61.5 % of the sectors improve their profits with this policy